2019
DOI: 10.3389/fpls.2018.01972
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Clathrin-Coated Vesicles From Arabidopsis thaliana Seedlings

Abstract: Clathrin coated vesicles (CCVs) mediate endocytosis of plasma membrane proteins and deliver their content to the endosomes for either subsequent recycling to the plasma membrane or transport to the vacuole for degradation. CCVs assemble also at the trans-Golgi network (TGN) and is responsible for the transport of proteins to other membranes. Oligomerization of clathrin and recruitment of adaptor protein complexes promote the budding and the release of CCVs. However, many of the details during plant CCV formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Further to this, digestion of the cell wall has been shown to result in intracellular aggregation of certain EAPs (Kang et al, 2003). However, the average CCV size closely matches that of biochemically purified CCVs from plant tissues (Mosesso et al, 2018;Reynolds et al, 2014), suggesting that CCVs in both contexts are formed in a similar fashion. A further limitation is accessibility to only the top view of the CCV, which means that hallmark features of the CME, such as the highly curved neck of CCVs, are obstructed by the vesicle itself.…”
Section: Unroofing Metal Replicamentioning
confidence: 84%
See 1 more Smart Citation
“…Further to this, digestion of the cell wall has been shown to result in intracellular aggregation of certain EAPs (Kang et al, 2003). However, the average CCV size closely matches that of biochemically purified CCVs from plant tissues (Mosesso et al, 2018;Reynolds et al, 2014), suggesting that CCVs in both contexts are formed in a similar fashion. A further limitation is accessibility to only the top view of the CCV, which means that hallmark features of the CME, such as the highly curved neck of CCVs, are obstructed by the vesicle itself.…”
Section: Unroofing Metal Replicamentioning
confidence: 84%
“…When EM approaches are combined with protocols for the enrichment of CCVs from plant tissues, as described in detail by Mosesso et al (2018) and Reynolds et al (2014), one can begin to define the molecular anatomy of the plant CCV. The disadvantage of examining CCVs isolated from plant tissues is that the preparation could be a mixture of PM-and trans-Golgi network (TGN)-derived CCV populations.…”
Section: Electron Microscopy Methods; Characterization Of Cme At the Ultrastructural Levelmentioning
confidence: 99%
“…By using the same sample preparation for biochemically isolated CCVs, we could directly compare them to specific CCV populations visualized inside cells. While we found that there were small differences in the sizes of endocytic and isolated CCVs, this is likely due to the fact that the isolated CCV preparations from whole cell lysates contain a mixture of CCVs derived from different origins -clathrin-mediated endocytosis and the early endosome/trans-Golgi network (22,27,28). We then validated our high throughput pseudo 3D analysis by applying it to metal replicas of unroofed cells carrying an inducible loss of endocytic membrane bending.…”
Section: Discussionmentioning
confidence: 77%
“…The data reported here reflects the content of CCVs isolated from undifferentiated, rapidly dividing and expanding Arabidopsis suspension cultured cells under conditions amenable to tissue culture. Future experiments probing CCV content in other cell and tissue types under varying conditions or in different genetic backgrounds might apply our isolation methodology (Reynolds et al, 2014) using seedlings as a sample source as recently described (Nagel et al, 2017;Mosesso et al, 2019).…”
Section: Discussionmentioning
confidence: 99%